Quantification of gas-assisted evaporation in minichannels with negative wall superheats. (March 2019) - Wu, Hung-Yi; Fu, Ben-Ran; Pan, Chin
Highlights: Gas-assisted evaporation for negative Δ Tsat was demonstrated quantifiably. Convective evaporation was dominant while Δ Tsat  < 0. Convective boiling was dominant while Δ Tsat  > 0. Maximum HTE of 275% is demonstrated at Δ Tsat  = −3.2 °C. Evaporation efficiency correlation involving mechanisms of convective evaporation and convective boiling is developed. Abstract: The present study quantifies the gas-assisted evaporation of ethanol in two parallel minichannels with negative wall superheats using helium as the auxiliary gas. At the exit of minichannels, an innovative gas – liquid separation and vapor condensation device is designed to measure the ethanol evaporated. The experimental results demonstrate that both the gas-assisted evaporation and mixing effects are significant mechanisms responsible for the significant enhancement of heat transfer with the introduction of helium gas in ethanol flow. For the present study, the maximum heat transfer enhancement of 275% is demonstrated under the condition of ethanol flow rate of 0.028 m/s, helium flow rate of 0.833 m/s, and wall superheat of −3.2 °C. Under such a condition, the gas-assisted evaporation contributes about 40% of total heat transfer rate. Flow visualization and exit quality measurement reveal that the phase change mechanism is dominated by convective evaporation in the region with negative wall superheat, while it is dominated by convective boiling under the conditions with positive wall superheat. The evaporation efficiency increases with decrease in ethanol flow rate, increases in helium flow rate and wall superheat. An empirical correlation for the evaporation efficiency is, thus, developed.